UNDERSTANDING OF THE ‘NATURE OF SCIENCE’ AMONG UNDERGRADUATE STUDENTS AT MUTAH UNIVERSITY IN JORDAN - Samara, Nawaf Ahmad (European Scientific Journal, ESJ, 2015)
The current study aimed at investigating Understanding of the ‘Nature of Science’ among undergraduate Students at Mutah University in Jordan and its relation with some variables. The sample of the study consisted of 392 undergraduate students, 274 females and 118 males who were chosen randomly from faculty of science and faculty of educational sciences in the academic year (2013/2014). To collect data, instrument which consisted of 23 items arranged into 5 domains covering various aspects of the nature of science was applied. The results showed that the level of understanding the nature of science among science and educational science students was of medium level with mean percentage (59.36). There were statistical differences found in the understanding of the nature of science among students due to the variable of student’s gender in favor of females, while the results showed no statistical differences attributed to variable of college. The research ended by suggesting several recommendations and further studies related to the nature of science for improving the teaching of NOS in high schools and college classrooms.